The Cambridge introduction to the American short story - Scofield, Martin (Cambridge University, 2013)
This wide-ranging introduction to the short story tradition in the United States of America traces the genre from its beginnings in the early nineteenth century with Irving, Hawthorne and Poe via Fitzgerald, Hemingway and Faulkner to O'Connor and Carver. The major writers in the genre are covered in depth with a general view of their work and detailed discussion of a number of examples of individual stories. The Cambridge Introduction to the American Short Story offers a comprehensive and accessible guide to this rich literary tradition. It will be invaluable to students and readers looking for critical approaches to the short story and wishing to deepen their understanding of how authors have approached and developed this fascinating and challenging genre. Further reading suggestions are included to explore the subject in more depth. This is an invaluable overview for all students and readers of American fiction."--Publisher's description.